Origin and development of film archive activity in Spain. Implementation and uniqueness of Spanish film archive map on the new digital environment (1954-2012). - García Casado, Pablo; Alberich Pascual, Jordi (Historia y Comunicación Social, 2014)
This article makes the genealogical study of the current Spanish film archive map, which is inhabited by fifteen regional film archives, plus three local and one state. We explored the beginnings of film preservation in the 20s in Spain, and how that desire breaks through with difficulty. After the interruption forced by the Civil War, we attend to its revitalization, culminating in the creation of the first National Film Archive (1954). Finally, we address the process of territorial expansion of film archive activity that opens with the Spanish Constitution of 1978.